(untitled) (Interdisciplinary Studies Journal, 2026)
The research investigated the relationships between teachers in the municipal public education system of Senador Canedo (GO), Generative Artificial Intelligence (GAI) resources (IAGen), and pedagogical-didactic work. The objective was to understand teachers’ perceptions regarding the use of technologies based on IAGen in the educational context. The methodological approach adopted a qualitative-quantitative design, grounded in the foundations of historical-dialectical materialism (HDM), through online questionnaires and semi-structured interviews. The data analysis, supported by critical theory of technology and by HDM, showed that, although teachers recognize the potential of IAGen for the development of didactic materials and the organization of the teaching and learning process, they also express concerns about the precarization of teaching work, the reproduction of educational disparities, and algorithmic biases. The scarcity of infrastructure, unequal access to technologies, and limited training on IAGen and educational processes reveal structural contradictions that influence pedagogical-didactic work. The research highlights the need for a critical appropriation of IAGen. It concludes that there is a need for an approach to IAGen and its inclusion in initial and continuing teacher education, in addition to other political elements.